2020
DOI: 10.3390/antibiotics9060300
|View full text |Cite
|
Sign up to set email alerts
|

A Silkworm Infection Model for In Vivo Study of Glycopeptide Antibiotics

Abstract: Glycopeptide antibiotics (GPAs) are drugs of last resort for treating infections by Gram-positive bacteria. They inhibit bacterial cell wall assembly by binding to the d-Ala-d-Ala terminus of peptidoglycan precursors, leading to cell lysis. Vancomycin and teicoplanin are first generation GPAs, while dalbavancin is one of the few, recently approved, second generation GPAs. In this paper, we developed an in vivo insect model to compare, for the first time, the efficacy of these three GPAs in curing Staphylococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 54 publications
1
22
0
1
Order By: Relevance
“…Insects possess a highly successful immune system that rapidly identifies pathogens and parasites and either kills them directly or immobilises them thus ensuring the survival of the host [ 1 ]. A wide range of structural and functional similarities exist between the insect immune response and the innate immune response of mammals [ 2 , 3 ] and, as a result, a wide variety of insects ( Galleria mellonella , Drosophila melanogaster , Manduca sexta , Bombyx mori ) is now used as in vivo models for assessing microbial virulence or for evaluating the in vivo efficacy and toxicity of antimicrobial compounds [ 4 , 5 , 6 , 7 ]. Larvae of the greater wax moth ( Galleria mellonella ) are widely used in academia and industry and in many cases generate results comparable to those that can be obtained using mammals [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insects possess a highly successful immune system that rapidly identifies pathogens and parasites and either kills them directly or immobilises them thus ensuring the survival of the host [ 1 ]. A wide range of structural and functional similarities exist between the insect immune response and the innate immune response of mammals [ 2 , 3 ] and, as a result, a wide variety of insects ( Galleria mellonella , Drosophila melanogaster , Manduca sexta , Bombyx mori ) is now used as in vivo models for assessing microbial virulence or for evaluating the in vivo efficacy and toxicity of antimicrobial compounds [ 4 , 5 , 6 , 7 ]. Larvae of the greater wax moth ( Galleria mellonella ) are widely used in academia and industry and in many cases generate results comparable to those that can be obtained using mammals [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This lepidopteran has also assumed great importance as a bioreactor capable of producing specific proteins such as silky biomaterials and molecules with biological activity [ 31 ]; the latter application is becoming particularly important in relation to the problem of the spread of different bacterial strains resistant to conventional antibiotics, and therefore, the lepidopteran is becoming important for the consequent search for natural compounds with antimicrobial activity [ 32 ]. Moreover, B. mori could be used as an alternative animal model for preclinical studies regarding infections by pathogens and the effectiveness of antibiotic therapies [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is the case of the recent work of Chen et al (2019) , who reported the effect of IONPs carrying vancomycin on C. difficile in mice infection model, demonstrating that nanoconjugated vancomycin exerted a therapeutic effect higher than free vancomycin, reducing intestinal inflammation, facilitating mucosal viability, and limiting the antibiotic side effects on intestinal microbiota. Our next goal is to test NP-TEICO and NP-VANCO in the invertebrate infection model that we have recently developed for comparing GPA efficacy in curing in vivo infections ( Montali et al, 2020 ). We employed easy-to-handle larvae of the silkworm Bombyx mori infected by S. aureus .…”
Section: Discussionmentioning
confidence: 99%